N-Type field effect transistors based on rigid rod and liquid crystalline alternating copoly(benzobisoxazole) imides containing perylene and/or naphthalene - Kolhe, Nagesh B.; Asha, S. K.; Senanayak, Satyaprasad P.; Narayan, K. S. (Journal of Physical Chemistry B, 2010)
The synthesis, characterization, and device studies of poly(benzobisoxazole imide)s containing perylene or naphthalene units in an alternating fashion with the oxazole unit are described. Photoinduced energy transfer and charge separation were studied in methanesulfonic acid (MSA) solution via absorption, excitation, and steady-state fluorescence studies. Excitation of the bisoxazole moiety resulted in enhanced emission from the perylene bisimide unit as a result of FRET (Forster resonance energy transfer). The influence of the imide substitution into the linear chain of poly(benzobisoxazole) (PBO) on its solid-state packing was examined by wide-angle X-ray diffraction (WXRD) analysis. Bottom contact field effect transistors (FET) based on thermally annealed polymer films were fabricated and studied. The polymers showed n-type charge transport and current modulation with an on/off ratio greater than 10(2). It was observed that the FETs consisting of the random copolymer of bisoxazole containing both perylene as well as naphthalene bisimide units had higher performance parameters such as better mobility (mu e) and I(on)/I(off) ratio compared to those of the pristine systems.

Structure engineering of naphthalene diimides for improved charge carrier mobility: self-assembly by hydrogen bonding, good or bad? - Kolhe, Nagesh B.; Devi, R. Nandini; Senanayak, Satyaprasad P.; Jancy, B.; Narayan, K. S.; Asha, S. K. (Journal of Materials Chemistry, 2012)
Two families of naphthalene diimide (NDI) derivatives were compared and contrasted for the effect of self-assembly on charge carrier transport. One series of NDI derivatives had a terminal phenyl ring attached to a hexyl spacer substituted naphthalene core either through an ester or an amide linkage (NDI-E and NDI-A, respectively), while the other series had a 3,4,5-tridodecyloxy phenyl unit (NDI-E3, NDI-A3) instead of the terminal phenyl unit. Solution processed thin films of these molecules exhibited n-type charge transport characteristics in a bottom gate top contact organic field effect transistor (OFET) geometry. The amide derivatives showed evidence of self-organization with observation of red shifted aggregate emission in solution as well as solid state. Variable temperature FTIR studies in the solid state confirmed the existence of strong hydrogen bonding which could be broken only at very high temperature. However, contrary to expectations, the NDI ester derivatives showed better device efficiency with electron mobilities in the range 8.5 x 10(-3) to 2 x 10(-2) cm(2) V-1 s(-1) and on/off ratio similar to 10(4). The thin film crystallinity and morphology of NDI-E and NDI-A were examined through X-ray diffraction and atomic force microscopy (AFM). The correlation of crystallinity, hydrogen bonding and charge carrier mobility was studied using energy minimized structures from density functional theory (DFT). The higher electron mobility of ester linked NDI derivatives over the amide linked ones was attributed to the freedom in charge transport pathways offered by a three dimensional crystalline organization in the ester compared to the restricted directional hydrogen bonding interaction in the amide derivatives.

Naphthalene diimide copolymers with oligo(p-phenylenevinylene) and benzobisoxazole for balanced ambipolar charge transport - Kolhe, Nagesh B.; Ashar, A. Z.; Narayan, K. S.; Asha, S. K. (Macromolecules, 2014)
A series of alternating and random donor (D)–acceptor (A) copolymers based on naphthalene diimide (NDI) as the acceptor and oligo(p-phenylenevinylene) (OPV) or benzobisoxazole (BBO) as the strong and weak donor, respectively, were designed and synthesized by Suzuki coupling and Horner–Wadsworth–Emmons polymerization. The effect of the varying donor strength of OPV and BBO on the photophysical, electrochemical, and semiconducting properties of the polymers was investigated. Absorption and emission spectra recorded for dilute chloroform solution and thin film showed increased intramolecular charge transfer for NDI-alt-OPV polymer compared to NDI-alt-BBO polymer. Cyclic voltammetry studies along with DFT (density functional theory) studies at the B3LYP/6-31g* level gave insight into the energy level (HOMO/LUMO) and molecular orientation of donor and acceptor along the polymer backbone. NDI-alt-OPV polymer exhibited rigid coplanar structure with extended π-conjugation which induced backbone planarity and crystallinity to the polymer. The inherent poor solubility of the NDI-alt-BBO prevented further device characterization of this polymer. Random copolymer having maximum 30% incorporation of BBO comonomer in NDI-r-OPV/BBO was found to be soluble for further characterization. Compared to NDI-alt-OPV, lowering of both energy levels LUMO (∼0.2 eV) and HOMO (∼0.5 eV) was observed for both NDI-alt-BBO and the NDI-r-OPV/BBO. Bottom gate–top contact organic field effect transistors (OFETs) of NDI-alt-OPV exhibited balanced ambipolar charge transport with average electron and hole mobility of 3.09 × 10–3 cm2 V–1 s–1 and 2.1 × 10–3 cm2 V–1 s–1, respectively, whereas the random copolymer incorporating both OPV and BBO units NDI-r-OPV/BBO showed dominant n-type charge transport with moderate 4 × 10–4 cm2 V–1 s–1 average electron mobility. The present work thus highlights the structure–property relationship and the electronic tunability required in this class of NDI-based polymers to produce ambipolar transistors.

Improved all-polymer solar cell performance of n-type naphthalene diimide-bithiophene P(NDI2OD-T2) copolymer by incorporation of perylene diimide as coacceptor - Sharma, Sandeep; Kolhe, Nagesh B.; Gupta, Vinay; Bharti, Vishal; Sharma, Abhishek; Datt, Ram; Chand, Suresh; Asha, S. K. (Macromolecules, 2016)
Naphthalene diimide-bithiophene P(NDI2OD-T2) is a well-known donor-acceptor polymer, previously explored as n-type material in all-polymer solar cells (all-PSCs) and organic field effect transistor (OFETs) applications. The optical, bulk, electrochemical, and semiconducting properties of P(NDI2OD-T2) polymer were tuned via random incorporation of perylene diimide (PDI) as coacceptor with naphthalene diimide (NDI). Three random copolymers containing 2,2'-bithiophene as donor unit and varying compositions of naphthalene diimide (NDI) and perylene diimide (xPDI, x = 15, 30, and 50 mol % of PDI) as two mixed acceptors were synthesized by Stille coupling copolymerization. Proton NMR spectra recorded in CD Cl-3 showed that the pi-pi stacking induced aggregation among the naphthalene units could be successfully disrupted by the random incorporation of bulky PDI units. The newly synthesized random copolymers were investigated as electron acceptors in BHJ all-PSCs, and their performance was compared with P(NDI2OD-T2) as reference polymer. An enhanced PCE of 5.03% was observed for BHJ all-PSCs (all-polymer solar cells) fabricated using NDI-Th-PDI30 as acceptor and PTB7-Th as donor, while the reference polymer blend with the same donor polymer exhibited PCE of 2.97% efficiency under similar conditions. SCLC bulk carrier mobility measured for blend devices showed improved charge mobility compared to reference polymer, with PTB7-Th:NDI-Th-PDI30 blend device exhibiting the high hole and electron mobility of 4.2 x 10(-4) and 1.5 x 10(-4) cm(2)/(V s), respectively. This work demonstrates the importance of molecular design via random copolymer strategy to control the bulk crystallinity, compatibility, blend morphology, and solar cell performance of n-type copolymers.